Chorion tissue- and plasma-derived extracellular vesicles exhibit superior anti-inflammatory and chondroprotective effects - Livia K. Fecskeova; Jana Matejova; Lucia Slovinska; Jana Bzdilova; Zuzana Kozovská; Denisa Harvanova (Stem Cell Research & Therapy)
Abstract Background Extracellular vesicles (EVs) are the foundation of modern regenerative medicine using a cell-free approach. While current research mainly explores EVs from biological fluids and cell culture supernatants, tissue-derived EVs hold great promise, but remain largely underexplored. Since healthy placental tissues such as the chorion are widely available after full-term delivery, ethically unobjectionable, and possess exceptional regenerative potential, we sought to compare the biological effects of EVs derived directly from chorion tissue with those from chorion-derived mesenchymal stromal cell EVs and plasma EVs. Method We compared the biological impact of EVs from various sources (chorion tissue CHO-Ti, MSCs from chorion CHO-MSC and platelet-poor plasma PPP) and isolated by various techniques on the gene expression of osteoarthritic chondrocytes. Additionally, we assessed the effect of enriched soluble proteins of CHO-MSC and CHO-Ti secretome vs. their EVs. EVs were characterized by particle number and size (NTA), protein content (BCA assay) and immunophenotype (flow cytometry). Changes in gene expression of chondrocytes were quantified by RT-qPCR. Results CHO-Ti-EVs and PPP-EVs showed particularly beneficial effect on the inflammatory process, with their biological impact surpassing that of CHO-MSC-EVs. Chondroprotective markers COL2A and ACAN were robustly upregulated by CHO-Ti-EVs and PPP-EVs but showed only modest or variable increases with CHO-MSC-EVs. COMP expression, however, was specifically enhanced by CHO-MSC-derived components. Furthermore, our results also indicate that the therapeutic properties of the CHO-Ti secretome are exclusively linked to EVs. Among CHO-MSC-EVs, purification combined with UC resulted in the highest purity, however EVs purified by SEC presented a more favourable surface marker profile and better biological effects. The observed variability suggests that different EV preparations harbour distinct subpopulations that influence regulatory pathways differently and highlight the importance of EV source and isolation methodology in determining biological activity. Conclusion CHO-Ti-EVs showed promising effects on cartilage regeneration and inflammation modulation, suggesting they may represent a viable alternative to plasma- and CHO-MSC-EVs. Moreover, the chorion represents a readily accessible and abundant source of perinatal tissue obtainable non-invasively after full-term delivery, further supporting the translational potential of CHO-Ti-EVs.